[Spot where John King of the Burke and Wills expedition was found]
King was a member of the tragic Burke and Wills exploration party. After their deaths he was assisted by Aborigines and survived a further three and a half months before being found by a party searching for the lost explorers.
Title devised by cataloguer from caption on negative bag.
Condition: Good.
This is a copy made by the National Library of Australia from an original that was lent for copying.
Part of a collection of negatives depicting members of the Arden family, their participation in war, outback scenes etc.
"Spot marked where Mr King was found of Burke & Wills exped."--negative bag.
Digital master available
Keywords: King, John, -- 1838-1872.; Historic sites -- Cooper Creek Region (Qld. and S.A.) -- Photographs; Cooper Creek Region (Qld. and S.A.) -- Photographs